Hearing, speech, and language in survivors of severe perinatal asphyxia. Issue 4 (April 1981) - D'Souza, S W; McCartney, E; Nolan, M; Taylor, I G
Abstract : Hearing, speech, and language were studied in 26 children who survived severe perinatal asphyxia. The results of hearing tests showed that most children had a favourable outcome. Only 1 child had sensorineural deafness. Hearing loss in 6 others was due to middle-ear disease which resolved after treatment, and on retesting was found to be normal. The study also showed that neither gentamicin treatment nor incubator noise seemed to affect hearing. The results of speech and language assessment were less encouraging and about one-third of the children without serious mental or physical handicap had deficits in speech and language. It is suggested that the quality of life in such children could be improved if these deficits were detected early and adequately treated.